Simulation of transient processes in low-frequency channel of the semiconductor regulated compensator - Levon, O. O. (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The simulation of transient processes in lowfrequency channel of the semiconductor twochannel regulated compensator of inactive components of total power is presented in given article. New control methods for two-channel compensator that allow to provide a high performance of the converter in the changing character of the load are proposed. Conclusions of obtained results are presented.

У статті розглянуто моделювання перехідних процесів в низькочастотному каналі напівпровідникового двоканального регульованого компенсатора неактивних складових повної потужності. Запропоновано методи прогнозного керування двоканальним компенсатором, які дозволяють забезпечити високі динамічні характеристики компенсатора при зміні характеру навантаження. Представлені результати моделювання, зроблені висновки.
Моделювання перехідних процесів у низькочастотному каналі напівпровідникового регульованого компенсатора
Keywords: power electronics; reactive power control; active power filter; thyristor binary compensator; силова електроніка; контроль реактивної потужності; силовий активний фільтр; двомостовий тиристорний випрямляч